2020
DOI: 10.1038/s41598-020-62747-9
|View full text |Cite
|
Sign up to set email alerts
|

TAS2R38 is a novel modifier gene in patients with cystic fibrosis

Abstract: The clinical manifestation of cystic fibrosis (CF) is heterogeneous also in patients with the same cystic fibrosis transmembrane regulator (CFTR) genotype and in affected sibling pairs. Other genes, inherited independently of CFTR, may modulate the clinical manifestation and complications of patients with CF, including the severity of chronic sinonasal disease and the occurrence of chronic Pseudomonas aeruginosa colonization. The T2R38 gene encodes a taste receptor and recently its functionality was related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 46 publications
0
25
0
Order By: Relevance
“…Interestingly, a recent study has demonstrated that the frequency of the PAV allele of TAS2R38 was significantly reduced not only in the CF population with nasal polyps requiring surgery, but also in CF patients with chronic pulmonary colonisation by P. aeruginosa. These data suggest a role for TAS2R38 as a novel modifier of sinonasal disease severity and of pulmonary P. aeruginosa colonisation in people with CF [ 95 ]. Similar to that observed in the upper respiratory tract, TAS2R-dependent defence mechanisms were detected in its lower parts [ 96 , 97 ].…”
Section: Extra-oral Expression Of the Bitter Taste—role In (Patho)physiological Processesmentioning
confidence: 99%
“…Interestingly, a recent study has demonstrated that the frequency of the PAV allele of TAS2R38 was significantly reduced not only in the CF population with nasal polyps requiring surgery, but also in CF patients with chronic pulmonary colonisation by P. aeruginosa. These data suggest a role for TAS2R38 as a novel modifier of sinonasal disease severity and of pulmonary P. aeruginosa colonisation in people with CF [ 95 ]. Similar to that observed in the upper respiratory tract, TAS2R-dependent defence mechanisms were detected in its lower parts [ 96 , 97 ].…”
Section: Extra-oral Expression Of the Bitter Taste—role In (Patho)physiological Processesmentioning
confidence: 99%
“…Apart from these structural predispositions, infection with P. aeruginosa clearly induced comparable lipid peroxidation in both wt and CFTR-knockout mice, and this was reproduced in isolated human airway epithelial cells expressing wtCFTR or F508del-CFTR. The recently identified novel modifier gene TAS2R38 that was identified in patients with cystic fibrosis, may have a significant impact on chronic lung colonization by P. aeruginosa [30,31]. Lipid peroxidation induced ferroptotic cell death that could be antagonized by antioxidants and ferrostatin-1.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, another CF modifier gene, SLC6A14, affected the attachment of P. aeruginosa in both mice and humans, since it transports a bacterial attachment-promoting metabolite (l-arginine) out of the host ASL [45]. More recently, Castaldo et al related the T2R38 genotype to the severity of sinonasal disease and the occurrence of P. aeruginosa pulmonary colonisation in 210 CF patients, suggesting that T2R38, which encodes a taste receptor, is a novel modifier gene in CF [46]. These and other modifier genes contribute to the diversity of CF disease, contributing to P. aeruginosa pathogenesis and the adaptation of the bacterium to the host environment.…”
Section: Introductionmentioning
confidence: 99%